Channel adjustment after artificial neck cutoffs in a meandering river of the Zoige basin within the Qinghai-Tibet Plateau, China - Li, Zhiwei; Gao, Peng (Catena (Giessen), 2019)
Neck cutoff is an essential process that significantly changes the morphodynamic characteristics of a meandering bend. In reality, however, observing natural processes of a neck cutoff is very difficult. In this study, we artificially triggered neck cutoffs by excavating a 0.4 m (width) × 0.5 m (depth) ditch to connect the beginning and ending of two highly convoluted bends along a meandering tributary of the upper Black River, a major tributary of the Upper Yellow River situated in the northeastern side of the Qinghai-Tibet Plateau in China. Our morphologic and hydraulic measurements in summers of 2013, 2014, 2016, and 2017, the subsequent hydraulic-geometry analysis, and three-dimensional simulation showed that both artificial ditches expanded fast to the size comparable to the former channel in a three-year period and the oxbow channel was disconnected from the former channel quickly, though sediment supply may be limited in this area. The morphological adjustment was featured by (1) distinct temporal trends of the development of the width/depth ratio between the two cutoff channels, (2) different diversion factors of the total discharge to the cutoff channel, and (3) diverse interaction patterns between cutoff and former channels. These discrepancies were supported by simulated different three-dimensional velocity distributions in the two cutoff channels, suggesting the importance of the clustered local velocities. Comparing these results with those reported in earlier studies showed that besides channel slope, unit stream power, and bank strength, the diversion angle between the cutoff and former channel played an important role in controlling channel adjustment. The discrepancy of the adjustment processes between the cutoff channel in this study and those in two previous ones revealed that channel adjustment after neck cutoff behaved differently under different physical settings and require more field-based studies. •This was the first study on meander rivers in the Qinghai-Tibet Plateau of China.•We measured three-year morphological adjustments of two meander bends after artificial neck cutoffs.•Rates of channel adjustments were mainly controlled by the diversion angle at the entrance of the cutoff channel.•Cutoff channels in this area may adjust their morphology quickly to the pre-cutoff conditions within three years.